A classical heuristic algorithm implementation for logistic analysis of waste collection problem: A case of Addis Ababa Arada Subicty - Achamu , Achamu; Berhan , Eshetie (Zede Journal of Ethiopian Engineers and Architects, 2023)
This paper intended to implement classical algorithms for logistic problem especially in revers logistic by using waste collection process to demonstrate. Along with its strategic nature and possibility for realization using analytical method, waste collection process considered as a vehicle routing problem, which is beyond solid waste management, instead a city logistic problem where optimization is demanding. For the case problem, mixed integer programming mathematical model deployed to node routing problem capacitated vehicle routing with the objective of minimizing total collection cost. Local search based on 2-Opt and Or-Opt improvement heuristics used to solving model based on initial solution obtained from Clark and Wright (saving method). Model relaxed to both Hamilton cycle and Hamilton path to accompany case problem and verified by problem instant with optimal solution cited. Due to relative operational data availability, Aradasubcity considered and coordinate of waste bin obtained using geodetic information on the Google earth while problem parameters determined based on the secondary data. . Model validation done using distance traveled and utilization of vehicles in the route and substantial result obtained with a saving of about 29.453 % in kilometers traveled per year and an increase of vehicle utilization from 68.19 % to 95.46% for each route. The finding shows a need of revision on the current practices of waste collection process in one hand and how classical heuristic are both potential and essential for solving problem of interest in the other hand.